2021
DOI: 10.1002/rmv.2278
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Parkinson's disease on manifestations and outcomes of Covid‐19 patients: A systematic review and meta‐analysis

Abstract: Summary Parkinson's disease (PD) patients who contracted Coronavirus disease 2019 (Covid‐19) had a decline in motor functions; nevertheless, there is limited evidence on whether PD patients have a higher risk for contracting Covid‐19 or have worse outcomes. This is the first systematic review and meta‐analysis to review the impact of PD on the prognosis of Covid‐19 patients. We performed a systematic search through seven electronic databases under the recommendations of the Preferred Reporting Items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…In a recent meta-analysis, the hospitalization rate for the PD patients infected with SARS-CoV-2 is calculated to be 39.89%, while the mortality rate to be 25.1%. Even the prevalence and severity of the COVID-19 disease including the mortality are considered to be higher than the general public [67]. Other disorders are found more frequent in the PD patients such as dyspnea, which is a respiratory dysfunction due to the muscle weakness and inadequate respiration excursion and found in 39% of the patients [69].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis, the hospitalization rate for the PD patients infected with SARS-CoV-2 is calculated to be 39.89%, while the mortality rate to be 25.1%. Even the prevalence and severity of the COVID-19 disease including the mortality are considered to be higher than the general public [67]. Other disorders are found more frequent in the PD patients such as dyspnea, which is a respiratory dysfunction due to the muscle weakness and inadequate respiration excursion and found in 39% of the patients [69].…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…Parkinson's disease (PD) is a neurodegenerative condition that affects people for a long time involving the CNS and especially affects the motor system. In several studies, it has been reported that the individuals suffering from PD are likely to be more vulnerable to the neurological disorder manifestation in COVID-19 disease [67,68]. In a recent meta-analysis, the hospitalization rate for the PD patients infected with SARS-CoV-2 is calculated to be 39.89%, while the mortality rate to be 25.1%.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…21 We used a random effects model in all the analysis due to presence of heterogeneity estimated by a p value of < 0.1 or I 2 > 50. 22 , 23 , 24 We further assessed publication bias if 10 or more studies were represented in one outcome using the two‐tailed Egger's test and publication bias was evident when p value < 0.1. 25 …”
Section: Methodsmentioning
confidence: 99%
“…El-Qushayri et al subsequently performed a systematic review and meta-analysis of Covid-19 in PwP ( El-Qushayri et al, 2021 ). Four studies which reported prevalence of Covid-19 in a total of 6878 PwP were included in the analysis.…”
Section: Covid-19 Prevalence In Parkinson's Diseasementioning
confidence: 99%
“…More recently, four systematic reviews and meta-analyses have helped to clarify risk. El-Qushayri and colleagues performed a systematic review which included 13 studies, encompassing 8649 PD patients and 88,710 controls ( El-Qushayri et al, 2021 ). Hospitalization was reported in eight studies (263 patients) with a pooled rate of 39.89% for PwP (95% CI: 27.09–58.73).…”
Section: Covid-19 Outcomes In Parkinson's Diseasementioning
confidence: 99%